Behavioral Intention and Level of Usage on Convergence Media training Platform on Journalism University Students of Private Universities in Sichuan, China - Liu, Yu; Phongsatha, Thanawan (Scholar: Human Sciences, 2023)
This study aims to investigate the factors that affect students’ behavioral intention and utilization of behavior in the convergence media training platform and to recommend cultivating converged media talents. Taking into account the development of the convergence media training platform, the Theory of Planned Behavior, the Technology Acceptance Model, and the Unified Theory of Plan and Technology Acceptance and Use were set out. The relationship between seven variables including Perceived Usefulness, Perceived Ease of Use, Attitude, Performance Expectation, Behavioral Intention, Social Impact, and Use Behavior was hypothesized. Four hundred and eighty (480) students from three colleges in Sichuan, China were the research samples. The Structural Equation Model (SEM) was utilized to examine the relationship between the variables. Moreover, the consequence revealed that most variables except the relationship between Perceived Ease of Use and Perceived Usefulness as well as Perceived Ease of Use and Attitude did not find a relationship among them. It is possible that students did not find the media convergence platform to be beneficial or simple to operate. In turn, It had no positive influence on attitudes. Hence, it is recommended that teachers and relevant departments strengthen communication and contact with the industry, provide students with more professional teaching content and practical skills training, cultivate a positive social environment, and enhance students’ learning attitude and learning efficiency.